Pemerolehan Bunyi Konsonan pada Anak Attention Deficit Hyperactivity Disorder (ADHD) dengan Latar Belakang Bilingual - Aburizal Sadam Habibi; Abdul Syukur Ghazali; Roekhan Roekhan; Nurchasanah Nurchasanah (Graduate School of Universitas Negeri Malang, 2022)
Abstract: The purpose of this study was to determine the acquisition of consonants that occur in children with ADHD with a bilingual background. This study uses a qualitative approach that aims to describe and explain the acquisition of consonants in children with special needs. This type of research is case study research. This study used a longitudinal design with research subjects only in one child. The results of this study are that Aza mastered 16 Indonesian consonant phonemes which were realized into inhibitory contoids [p,b,t,d,ḍ,k,j,g,?], nasal [m,n,ṇ,ƞ,ň], fricative [s,h], Africative [c,j], and lateral [I]. However, among these sounds there are still sounds that are still fluctuating. The fluctuating sounds include fricative contoid [s] and lateral contoid [l]. Meanwhile, Aza has not mastered 5 Indonesian consonant phonemes, namely the fricative phonemes /f/, /v/, /z/, /x/ and /r/.Abstrak: Tujuan penelitian ini adalah untuk mengetahui pemerolehan bunyi konsonan yang terjadi pada anak ADHD dengan latar belakang bilingual. Penelitian ini menggunakan pendekatan kualitatif yang bertujuan untuk menjelaskan pemerolehan bunyi konsonan pada anak berkebutuhan khusus. Jenis penelitian ini adalah studi kasus serta desain longitudinal dengan subjek penelitian hanya pada satu anak. Hasil penelitian ini yakni Anak menguasai 16 fonem konsonan bahasa Indonesia yang terealisasi menjadi kontoid hambat [p,b,t,d,ḍ,k,j,g,?], nasal [m,n,ṇ,ƞ,ň], frikatif [s,h], afrikatif [c,j], dan lateral [I]. Namun, di antara bunyi tersebut masih ada bunyi fluktuatif yang meliputi kontoid frikatif [s] dan kontoid lateral [l]. Sementara itu, Aza belum menguasai lima fonem konsonan bahasa Indonesia, yaitu fonem frikatif /f/, /v/, /z/, /x/ dan /r/.